2019
DOI: 10.1002/adfm.201904349
|View full text |Cite
|
Sign up to set email alerts
|

2D Boron Sheets: Structure, Growth, and Electronic and Thermal Transport Properties

Abstract: The structures of boron clusters, such as flat clusters and fullerenes, resemble those of carbon. Various two‐dimensional (2D) borophenes have been proposed since the production of graphene. The recent successful fabrication of borophene sheets has prompted extensive researches, and some unique properties are revealed. In this review, the recent theoretical and experimental progress on the structure, growth, and electronic and thermal transport properties of borophene sheets is summarized. The history of predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 156 publications
(108 citation statements)
references
References 163 publications
(481 reference statements)
1
107
0
Order By: Relevance
“…From this table, it is observed that thermal conductivity of InSe is lower than that of graphene, phosphorene. The thermal conductivity of InSe is on the same magnitude as that of borophene 60 , however, the Young’s modulus of InSe is lower than that of borophene significantly 47 . The results implied InSe possesses the weaker phononic anharmonicity than borophene.…”
Section: Resultsmentioning
confidence: 95%
“…From this table, it is observed that thermal conductivity of InSe is lower than that of graphene, phosphorene. The thermal conductivity of InSe is on the same magnitude as that of borophene 60 , however, the Young’s modulus of InSe is lower than that of borophene significantly 47 . The results implied InSe possesses the weaker phononic anharmonicity than borophene.…”
Section: Resultsmentioning
confidence: 95%
“…2D layered materials, such as single layer graphene [16][17][18] , silicene 19,20 , phosphorene 21,22 , borophene 23,24 , and a series of other layered materials [25][26][27] , have been systematically investigated in scientific community for using as TE materials. Recently, 2D triphosphides are reported one after another with fascinating properties, raising great concern 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Heat dissipation is the most important factor affecting and limiting the performance of modern electronic devices [31,32,33,34,35,36]. Thus, how divacancies affect heat transport performance of graphene and graphene nanodevices is an important question.…”
Section: Introductionmentioning
confidence: 99%